Disease Burden of Neonatal Care Unit at Al-Bayda Medical Center Al-Bayda Libya - Younis , Kamala O.; Saed, Wafa J. (Al-Mukhtar Journal of Sciences, 2021)
This research was conducted to determine the number, disease pattern, and outcome of the patients admitted at the Neonatal Care Unit (NCU) at Al-Bayda medical center (AMC) in Libya. A retrospective cross-sectional descriptive study was carried out on all neonates admitted to the NCU between January 2008 and December 2008. The collected data include age, gender, mode and site of delivery, number of gestations, maturity, duration of stay, cause of admission, and outcome. Total infants delivered were 10075, 620 (6.1%) of them were admitted to NCU with a (6.15%) admission rate, 56.5% were male and 43.5% were female, of whom 613 (98.9%) were inborn and 519 (83.7%) were term neonates; 523 (84.4%) of total born were by normal vaginal delivery (NVD). 48.7% of total admissions occurred during the first 24 hours of life. The average length of hospital stay for term births was 5.6 days (SD 5.4) and for preterm 8.7 days (SD 8.55). The common causes of admission were neonatal jaundice (29.3%), followed by neonatal infections (17.6%) were prematurity accounts for (16.3%), and respiratory distress (11.1%). The majority of the admitted neonates improved and were discharged 517 (83.4%), 37(6%) left against medical advice (LAMA) and nineteen (3%) were referred to other specialized hospitals for further management. The neonatal mortality rate was 0.4%, and the overall hospital neonatal mortality rate was 7.6%. According to the cause-specific death rate analysis, prematurity was the most common cause of death (29.8%), followed by sepsis (17%) and birth asphyxia (12.8%). In conclusion, neonatal jaundice, infection, and prematurity complications were the leading causes of morbidity in neonates. The case-fatality rate was high for prematurity, sepsis, and birth asphyxia. Most of these etiologies are preventable to some extent by regular prenatal visits, healthy delivery practices, and timely referral to hospitals which can reduce NCU burden and improve outcomes